2016
DOI: 10.1002/term.2131
|View full text |Cite
|
Sign up to set email alerts
|

Translational issues for human corneal endothelial tissue engineering

Abstract: Corneal endothelial disorders collectively represent a significant healthcare burden in most developed nations, and corneal transplantation is currently the only treatment available for patients with poor visual acuity and corneal blindness secondary to endothelial failure. Although vision in these patients can be restored by transplantation, the global demand for donor human corneas is far in excess of what can be provided for by eye banks around the world, and this deficit is set to increase with an ageing g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
42
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 183 publications
0
42
0
3
Order By: Relevance
“…The worldwide shortage of donor corneal tissue for the treatment of corneal endothelial dysfunction necessitates the development of viable alternatives to the paradigm of one donor cornea being used for only one recipient (Mehta et al, 2019; Okumura et al, 2014b; Soh et al, 2017). Corneal endothelial cell (CEnC) dysfunction is the primary indication for corneal transplantation both in the United States and worldwide, and while endothelial keratoplasty represents a significant advance in the surgical management of corneal endothelial dysfunction, the worldwide shortage of surgical-grade donor corneas and the lack of adequately trained surgeons in the majority of countries, as well as a variety of associated intraoperative and postoperative complications, have significantly limited the impact of endothelial keratoplasty on visual impairment worldwide due to corneal endothelial dysfunction (Deng et al, 2015; Lass et al, 2017; Van den Bogerd et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The worldwide shortage of donor corneal tissue for the treatment of corneal endothelial dysfunction necessitates the development of viable alternatives to the paradigm of one donor cornea being used for only one recipient (Mehta et al, 2019; Okumura et al, 2014b; Soh et al, 2017). Corneal endothelial cell (CEnC) dysfunction is the primary indication for corneal transplantation both in the United States and worldwide, and while endothelial keratoplasty represents a significant advance in the surgical management of corneal endothelial dysfunction, the worldwide shortage of surgical-grade donor corneas and the lack of adequately trained surgeons in the majority of countries, as well as a variety of associated intraoperative and postoperative complications, have significantly limited the impact of endothelial keratoplasty on visual impairment worldwide due to corneal endothelial dysfunction (Deng et al, 2015; Lass et al, 2017; Van den Bogerd et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The LEC-CM could mimic the E12.5 environment in CEC differentiation by regulating FOXC1 through TGFb-2. 37 Therefore, in this part of the study, we examined the FOXC1 signaling pathway components involved in the regulation of CEC development. QPCR results showed that the expression of FOXC1 and PITX2 began to increase in the EB stage of differentiation after adding RA (Fig.…”
Section: Induction Of Pomps Into Cec-like Cells Is Regulated By the Tmentioning
confidence: 99%
“…Corneal endothelium, a monolayer of cells with a hexagonal structure beneath the Descemet membrane, maintains corneal transparency through the regulation of aqueous humor flow to the corneal stroma. 3,4 The Na þ -and K þ -dependent ATPase (Na þ /K þ -ATPase) expressed in the basolateral membrane of CECs is primarily responsible for the pumping function of the corneal endothelium. 5,6 Human CECs are arrested in the G1 phase of the cell cycle; therefore, CECs have a poor proliferative capability in vivo.…”
mentioning
confidence: 99%
“…As such, the “holy grail” of corneal treatment by endothelial stem cells continues to be assessed by a large number of international teams. Tissue engineered endothelial keratoplasty options using a thin layer of corneal stroma and cultured endothelial cells is another target, when irregularities in Descemet's membrane necessitates its replacement …”
mentioning
confidence: 99%
“…Tissue engineered endothelial keratoplasty options using a thin layer of corneal stroma and cultured endothelial cells is another target, when irregularities in Descemet's membrane necessitates its replacement. 18 Development of surgical treatments for corneal endothelial diseases has undergone a truly remarkable revolution in the last 20 years. Although there is still a worldwide shortage of donor corneas, the landscape is changing forever thanks to rapid advances in endothelial lamellar surgery and related science.…”
mentioning
confidence: 99%